51 STRUCTURAL REMODELING OF THE HEART IN RATS WITH ALDOSTERONISM: RESPONSE TO SPIRONOLACTONE OR DIETARY ZINC SUPPLEMENT. Issue 1 (1st January 2007) - Selektor, Y.; Sun, Y.; Thomas, M.; Weber, K. T.
Abstract : Purpose: Fibrosis contributes to an adverse structural remodeling of the failing heart. In morphologic terms, it presents as a perivascular/interstitial fibrosis of intramural coronary arteries and as microscopic scarring, a marker of necrotic cardiomyocyte death. Because these lesions are found in both the right and the left heart, a circulating substance has been incriminated (vis-è-vis a hemodynamic factor). In rats with aldosteronism, such as structural remodeling with fibrosis is found throughout the heart and other organs, together with markers of oxidative stress and redox-sensitive transcription. We hypothesized that it is possible to attenuate the appearance of cardiac fibrosis in rats with aldosteronism by cotreatment with either an aldosterone receptor antagonist, spironolactone (Spiro), or a dietary Zn supplement (Zn + ), an antioxidant. Methods and Results: Eight-week-old male, uninephrectomized Sprague-Dawley rats received aldosterone via subcutaneous pump (0.75 μg/h) and 1% NaCl in their drinking water (ALDOST) for 4 weeks alone or together with either Spiro (150 mg/kg/d by gavage) or Zn + (1478.84 mg of Zn/kg chow). At 4 weeks, hearts were harvested for immunohistochemical detection of gp91 phox, a subunit of NADPH oxidase and source of superoxide, and histochemical assessment of fibrillar collagen using picrosirius red. In coronal sections taken from the minor axis of the heart, morphometric determination of collagen volume fraction (CVF) was assessed. In contrast to untreated, unoperated controls, there was increased tissue labeling for gp91 phox and an increase in cardiac CVF (1.3 ± 0.2 vs 4.5 ± 0.6%; p < .05) at 4 weeks of ALDOST that presented as a perivascular/interstitial fibrosis and microscopic scarring; CVF in hearts obtained from rats with Spiro cotreatment was no different from controls (1.3 vs 1.4 ± 0.3), and this included an absence of each form of cardiac fibrosis in both ventricles and gp91 phox labeling. With dietary Zn + supplement there was an attenuation, but not prevention, of cardiac fibrosis (3.6 ± 0.4%; p < .05 vs ALDOST). Conclusion: In association with aldosteronism, increased fibrillar collagen deposition as well as increased activity of gp91 phox was found in cardiac tissue. These effects were prevented by Spiro cotreatment or diminished by dietary Zn + supplementation to further implicate oxidative stress in the appearance of cardiac fibrosis in aldosteronism. Fibrosis is a surrogate marker of a previously altered redox state.